Content Transformation of the "Significant Other" Representation in a Transitive Society - Ryaguzova, Elena V. (Saratov State University, 2020)
The purpose of the study presented in the article is theoretical reflection on the meaningful transformation of the "Significant Other" representation in a transitive society. It describes the main attributes of a transitional society (instability, uncertainty, projectivity, multidirectionality, multivariability, innovativeness, etc.), indicating its institutional and value-related changes, their irreversibility, as well as unity of preservation and negation of rules, norms and values, old and new worldviews and world orders, their conflict and alternativeness. The study analyses features of personal socialization in a transitive society, highlights similarities and differences in the content, mechanisms and determinants of socialization. The author's attention is focused on qualitative changes in the representations of Significant Other, which are the result of individual's interaction with the Others, based not so much on perceptual processes, but rather on living and experiencing certain experiences and constructing existential meanings. It substantiates the increase in the number of representations of "Significant Other" in the modern society, due to expansion of communicative space, total globalization processes, development and dissemination of various information technologies. It is argued that meaningful content of the representation of "Significant Other", is, on the one hand, expanding, including a wider range of ideas about significant figures (familiar and unfamiliar in everyday life, symbolic and virtual), a variety of assessments and established relations to the world, Others and oneself, while, on the other hand, it is reduced and schematized, broken up into separate components of significance (referentiality, attraction, power), and sometimes depersonalized, losing the descriptive and evaluative attributes of individuality and uniqueness. The applied aspect of the problem under study is the possibility of using the obtained theoretical generalizations in the practice of socio-psychological support of a person in the process of socialization (including digital socialization) in a modern transitive society.